The influence of insulin on anticipation and consummatory reward to food intake: A functional imaging study on healthy normal weight and overweight subjects employing intranasal insulin delivery. Issue 18 (21st July 2022) - Wingrove, Jed; O'Daly, Owen; De Lara Rubio, Alfonso; Hill, Simon; Swedroska, Magda; Forbes, Ben; Amiel, Stephanie; Zelaya, Fernando
Abstract: Aberrant responses within homeostatic, hedonic and cognitive systems contribute to poor appetite control in those with an overweight phenotype. The hedonic system incorporates limbic and meso‐limbic regions involved in learning and reward processing, as well as cortical regions involved in motivation, decision making and gustatory processing. Equally important within this complex, multifaceted framework are the cognitive systems involved in inhibitory control and valuation of food choices. Regions within these systems display insulin receptors and pharmacologically increasing central insulin concentrations using intranasal administration (IN‐INS) has been shown to significantly reduce appealing food cue responsiveness and also food intake. In this work we describe a placebo‐controlled crossover pharmacological functional magnetic resonance imaging (fMRI) study that looks at how IN‐INS (160 IU) affects anticipatory and consummatory responses to sweet stimuli and importantly how these responses differ between healthy normal weight and overweight male individuals. This work shows that age matched normal weight and overweight (not obese) individuals respond similarly to both the anticipation and receipt of sweet stimuli under placebo conditions. However, increased central insulin concentrations produce marked differences between groups when anticipating sweet stimuli within the prefrontal cortex and midbrain as well as observed differences in the amygdala during consummatory responses. Abstract : This study probes anticipatory and consummatory responses to sweet solution using a fMRI paradigm which delivers liquid stimuli. This work shows that when brain insulin concentration is increased, using intranasal insulin administration, differences in these responses can be identified between lean and overweight individuals.